The Kaiser's web [large type] - Berry, Steve, 1955- (Berry, Steve, 1955- Cotton Malone novels ;, 2021)
"Two candidates are vying to become chancellor of Germany. Both harbor secrets and are on a collision course, all turning on the events of one fateful day--April 30, 1945--and what happened deep beneath Berlin in the Fürherbunker. Did Adolph Hitler and Eva Braun die there? Did Martin Bormann, Hitler's close confidant, manage to escape? And where did billions in Nazi wealth disappear to in the waning days of World War II? The answers will determine who becomes the next chancellor. Former Justice Department agent Cotton Malone discovers the truth about the fates of Hitler, Braun, and Bormann, that could not only transform Europe, but finally expose a mystery known as the Kaiser's web"--Page 4 of cover.